1896 R.I. Gen. Laws 372, tit. 14, ch. 110, § 4 - (:unkn) unknown (My University, 1896)
Every person who shall sell, expose for sale, or have in his possession with intent to sell, use or explode, or shall use or explode any fire cracker containing any explosive other than gunpowder, shall be fined not more than twenty dollars.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES